New host plant and distribution records for weevils of the genus Hydnorobius (Coleoptera: Belidae) - Ferrer, Maria Silvia (2010)
The association of Hydnorobius hydnorae (Pascoe) (Belidae: Oxycoryninae) with both species of the genus Prosopanche de Bary (Hydnoraceae), Prosopanche americana (R. Br.) Baillon and Prosopanche bonacinai Spegazzini, is reported, providing the first record of its occurrence on the latter. A new distribution record, from Southern Mendoza, is given for the plant P. bonacinai and for the two weevil species associated with it: Hydnorobius hydnorae and Hydnorobius parvulus (Bruch). Such cooccurrence of two species of Hydnorobius Kuschel on the same host plant is also recorded for the first time.